LOS SABERES POPULARES SOBRE LAS TECNOLOGÍAS COMUNITARIAS DE PESCA. ESTUDIO DE CASO EN LA COMUNIDAD CASTILLO DE JAGUA - García Dueñas, Roberto Yasiel (Riparia, 2017)
The need to safeguard the intangible cultural heritage of our communities is of paramount importance in these times of globalization. Hence the urgency of carrying out measures aimed at guaranteeing the viability of this heritage by identifying, documenting, researching, preserving, protecting, promoting and valuing it in its various aspects, as set out in the Convention for the Safeguarding of Intangible Cultural Heritage In 2003. The present work assesses the popular knowledge about the community fishing technologies of the Castillo de Jagua community from a sociocultural perspective, where they analyze the interrelations that are generated between these, socio-cultural practices and the traditional knowledge of the members of the community, to constitute these, expressions of the traditional popular culture.